The nerve lesion in the carpal tunnel syndrome. - Sunderland, S (1976)
The relative roles of pressure deformation and ischaemia in the production of compression nerve lesions remain a controversial issue. This paper concerns the genesis of the structural changes which follow compression of the median nerve in the carpal tunnel. The initial lesion is an intrafunicular anoxia caused by obstruction to the venous return from the funiculi as the result of increased pressure in the tunnel. This leads to intrafunicular oedema and an increase in intrafunicular pressure which imperil and finally destroy nerve fibres by impairing their blood supply and by compression. The final outcome is the fibrous tissue replacement of the contents of the funiculi.